IMAGINE THERE’S A HEAVEN REASONABLE RELIGION, RELIGIOUS REASON - Ramon Nadres (Arete, 2012)
Religious fundamentalism, on the one hand, as manifested in terrorist activity and extreme rationalism which leads to atheism on the other seem to be untenable choices for any honest man. Both put faith and reason at odds with one another. If neither is acceptable, then there must be a middle way. Thomas Aquinas has spoken about the medium virtutis, the golden mean, when it comes to virtuous acts, which avoid vicious extremes in any moral act. How do we find this medium virtutis between faith and reason? After looking at prudence as the recta ratio agibilium and seeing that the guide for the recta ratio is the truth, we then discover that, for moral truth, which is involved in the medium virtutis of faith and reason, the bridging criterion is human nature, and that reason spans not only the empirical realm, but the philosophical and supernatural realms as well.